SableSpMT a software framework for analysing speculative multithreading in Java. - Pickett, Christopher J. F. (Software engineering notes.)
Speculative multithreading (SpMT) is a promising optimisation technique for achieving faster execution of sequential programs on multiprocessor hardware. Analysis of and data acquisition from such systems is however difficult and complex, and is typically limited to a specific hardware design and simulation environment. We have implemented a flexible, software-based speculative multithreading architecture within the context of a full-featured Java virtual machine. We consider the entire Java language and provide a complete set of support features for speculative execution, including return value prediction. Using our system we are able to generate extensive dynamic analysis information, analyse the effects of runtime feedback, and determine the impact of incorporating static, offline information. Our approach allows for accurate analysis of Java SpMT on existing, commodity multiprocessor hardware, and provides a vehicle for further experimentation with speculative approaches and optimisations.